2020
DOI: 10.1158/2159-8290.cd-19-0811
|View full text |Cite
|
Sign up to set email alerts
|

Gain-of-Function RHOA Mutations Promote Focal Adhesion Kinase Activation and Dependency in Diffuse Gastric Cancer

Abstract: Diffuse gastric cancer (DGC) is a lethal malignancy lacking effective systemic therapy. Among the most provocative recent results in DGC has been that of highly recurrent missense mutations in the GTPase RHOA. The function of these mutations has remained unresolved. We demonstrate that RHOA Y42C , the most common RHOA mutation in DGC, is a gain-offunction oncogenic mutant, and that expression of RHOA Y42C with inactivation of the canonical tumor suppressor Cdh1 induces metastatic DGC in a mouse model. Biochemi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
79
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(98 citation statements)
references
References 67 publications
9
79
0
1
Order By: Relevance
“…Given the strong positive correlation of YAP hyperactivation with poor prognosis of GC, growing efforts are being made to target the Hippo–YAP pathway for treating GC (Calses et al, 2019; Huang et al, 2020; Jiao et al, 2014, 2018; Kang et al, 2011; Tang et al, 2019a; Zanconato et al, 2016; Zhang et al, 2020). We previously observed that YAP was up-regulated in GC, and such up-regulation was positively correlated with tumor stages (Jiao et al, 2014, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the strong positive correlation of YAP hyperactivation with poor prognosis of GC, growing efforts are being made to target the Hippo–YAP pathway for treating GC (Calses et al, 2019; Huang et al, 2020; Jiao et al, 2014, 2018; Kang et al, 2011; Tang et al, 2019a; Zanconato et al, 2016; Zhang et al, 2020). We previously observed that YAP was up-regulated in GC, and such up-regulation was positively correlated with tumor stages (Jiao et al, 2014, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is rare or less common to observe mutation or abnormal expression of the upstream tumor suppressor kinases (Zheng and Pan, 2019). For example, we and others have shown that YAP is hyperactivated in GC (Jiao et al, 2014; Kang et al, 2011; Zhang et al, 2020) and that constitutive activation of YAP drives GC development (Choi et al, 2018; Huang et al, 2020; Jiao et al, 2018); yet MST1/2 and LATS2 kinases seem to be normally expressed without any mutation in GC. These phenomena hint at the possibility of additional or alternative regulation of YAP activity beyond the canonical Hippo kinase cascade.…”
Section: Introductionmentioning
confidence: 96%
“…Gastric cancer has a high mortality rate, and threatens human life and health 33 . The extremely poor prognosis of patients with gastric cancer greatly promotes the development of an effective treatment measure 34 .…”
Section: Discussionmentioning
confidence: 99%
“…P29S-Rac1 is a fast cycling mutant with spontaneous activation and therefore acts as a gain-of-function mutation [26,27]. The Y42C mutation reduces both intrinsic-and GAP-stimulated GTP hydrolysis of RhoA, thereby enhancing the active GTP-bound form [28]. On the contrary, Wang et al proposed that the Y42C mutation decreased the level of the activated GTP-associated form of RhoA [29].…”
Section: Neuroendocrine Tumors and Rho Gtpasesmentioning
confidence: 99%